PSXVII-1 Real time determination of metabolic efficiency in cattle with infrared thermography. (7th December 2018) - Schaefer, A; Bench, C; Bollum, R; Cook, N; Crow, G; Maharjan, D; Ominski, K; Rodas-González, A; Thompson, S; von Gaza, H
Abstract: The cost of production and carbon footprint of beef cattle is dependent on the metabolic efficiency. Conventional methodology for measuring metabolic efficiency, including residual feed intake (RFI), is time consuming and expensive. Moreover, determinations are not often available until well into the growth cycle of the animal. Hence, the development of cost effective methods to measure efficiency is important. The objective of the present study was to use infrared thermography (IRT) in a rapid, non-steady state method to rank metabolic efficiency. Three studies were undertaken on 127 head of yearling Angus and crossbred bulls and crossbred steers. Standard protocols regarding the length of RFI tests (70 d) and delivery of a cereal-silage based diet which met or exceeded their growth maintenance requirements were followed. The IRT images (320 x 240 pixels) were collected during a 24h test on the orbital eye and cheek of all cattle (at a distance of 2 m at 90°) either before or following their RFI test. The correlation analysis between RFI and IRT demonstrated that animals with the lowest 50% cheek temperatures (28.8 C ± 0.75 (SD)) had RFI values of -0.1 kg.d -1 (more efficient) compared to animals displaying the higher 50% temperatures (32.7 C ± 1.7) with an RFI value of 0.14 kg.d -1 (P<0.01). The most efficient 10% of the animals with an RFI value of -0.96 kg.d -1 had an infrared temperature of 30.9 ± 2.4 C which was significantly lower (P<0.05) than the least efficient 10% of animals (RFI= 1.02 kg.d -1 ) with a temperature of 32.4 ± 1.82. In addition, several animals displaying aberrant health conditions were also identified with infrared which were not apparent with feed intake data. The current studies suggest thermal phenotypic measurements demonstrate utility in identifying animals displaying superior metabolic efficiency.